STRATEGY TO INCREASE THE TAX RATIO THROUGH DIGITAL ECONOMY TAXATION: REVIEW OF LESSONS FROM ASEAN COUNTRIES - Judijanto, Loso (Yayasan Nuraini Ibrahim Mandiri, 2024)
This study aims to investigate the effect of tax increase strategies on the Tax Revenue Ratio, moderated by the Digital Economy in Indonesia. The data used is panel data consisting of 60 observations over a specific period. The analysis was conducted using multiple linear regression methods and other statistical tests to examine the research hypotheses. The analysis results indicate that, although there are initially intriguing indications, there is insufficient statistical evidence to support a significant effect of the tax increase strategy on the Tax Revenue Ratio within the context of the sample studied. Similarly, the Digital Economy does not appear to have a significant influence on the Tax Revenue Ratio. Additionally, there is no significant moderating effect of the Digital Economy on the relationship between the tax increase strategy and the Tax Revenue Ratio. Nonetheless, this study's findings provide valuable insights for further understanding the dynamics between tax strategies, the digital economy, and the Tax Revenue Ratio. The policy implications of these findings underscore the need for further research and a deeper understanding of the factors influencing the Tax Revenue Ratio in Indonesia, particularly in facing the challenges and opportunities of the continuously evolving digital economy. Keywords: Tax Increase Strategy, Digital Economy, State Tax Revenue, Tax Policy, Digital Economy Dynamics